THE ROLE OF LEARNING INNOVATION HIGH ORDER THINKING SKILLS IN IMPROVING STUDENTS' ANALYTICAL ABILITIES IN PAI SUBJECTS AT ATHIRAH BONE ISLAMIC HIGH SCHOOL - Wa'ishah Mansur; Wardana Wardana; Nursyirwan Nursyirwan (Education Studies and Teaching Journal (EDUTECH), 2025)
This study explores the role of Higher Order Thinking Skills (HOTS) learning innovation in enhancing students’ analytical abilities within the context of Islamic Religious Education (PAI) at Athirah Bone Islamic High School. In the era of 21st-century education, fostering higher-order thinking is crucial to developing students’ critical, logical, and systematic thinking capacities. Employing a quantitative research design, data were collected through validated and reliable questionnaires. The findings reveal a consistently positive student response to the implementation of HOTS-based learning strategies, indicating that such approaches effectively support the development of analytical thinking. Furthermore, the study confirms a significant and positive relationship between HOTS learning innovation and students’ analytical skills. These results underscore the importance of integrating HOTS-oriented methods in Islamic education to foster deeper understanding and higher cognitive engagement among students. The study also highlights the need for institutional support, including continuous professional development for teachers, the availability of relevant instructional media, and the creation of a learning environment that nurtures critical and analytical thinking. This research contributes to the growing body of evidence on the effectiveness of HOTS in educational practice and offers practical implications for curriculum development and pedagogical innovation in religious education settings.